La “familizzazione” dell’impresa: alcune riflessioni sul familismo imprenditoriale in Brianza nella crisi economica attuale - Simone Ghezzi (EtnoAntropologia)
Drawing on a ethnographic research in an area characterized by a dense network of small family-run firms this article looks at the transformation of such enterprises and at their inner relations. It argues that family-run firms are a special kind of organization of production as family (non-commodified) labour and commodified labour are interwoven. Familistic relations, which permeates the enterprise and creates the basic conditions for its formation and functioning, is termed entrepreneurial familism. It sets the organizational structure of the firm and defines the strategies of the transmission of capital adopted by the entrepreneurs. The leader of a small family firm may decide to include or to exclude some kin members from the process of intergenerational succession in order to secure corporate earnings and good performance in the upcoming future. Yet, the choice of share redistribution and ultimately the planning of succession may be a highly contested business decision within the kin group. This form of unequal transmission of capital, based on gender, may leave painful scars within the family, undermining or even destroying personal relationships and kinship solidarity.